Local knowledge matters: understanding the decision-making processes of communities under climate change in Suriname - Smith, Gwendolyn; Chowenga, Mawie; Karsters, Jethro (Frontiers in Climate, 2024)
Introduction Traditionally, local communities have relied on practical observations accumulated over extended periods to inform their decision-making. This knowledge is now recognized as a viable solution for communities to adapt to climate change effectively. The impact of climate change brings an extra layer of complexity to local communities' detection- and decision-making processes, which needs to be better comprehended. Methodology Our study builds on the foundation of conflict resolution and examines the knowledge systems and corresponding decision-making processes of local communities living in urban, rural, and tropical forest regions of Suriname, South America. Results The mixed-method study showed that the autonomous decision-making processes of these communities are guided by their knowledge systems, intertwined with values and interests. Forest communities in remote locations rely solely on their robust knowledge base for crafting adaptation solutions, while urban and rural communities near the administrative centers develop adaptation strategies primarily considering their access to social networks and relative power. Discussion The study highlights local knowledge as the primary determinant for the direction communities take in adaptation, with tradeoffs becoming evident as communities navigate the broader social context. The recognition and integration of this knowledge emerge as a critical factor in enhancing climate change adaptation at the local level.